2021
DOI: 10.1111/nep.13847
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in COVID‐19: Identification of risk factors and potential biomarkers of disease in a large UK cohort

Abstract: Background COVID‐19 is associated with increased risk of acute kidney injury (AKI). Risk factors and biomarkers linked to AKI have now been recognized by national guidelines in the United Kingdom. This analysis aims to validate and expand the comorbidities and biomarkers associated with the presence and severity of AKI in these patients. Methods Data were extracted via structured query language for patients with COVID‐19 at University Hospital Southampton between 1 March and 10 June 2020. Demographics, comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…COVID-19 patients who are older, males, malnourished or diabetic are more prone to develop AKI. 15 In current study, patients with higher age had AKI more than patients with relatively lower age as also reported by other studies. 10,13,15 This may be due to immunocompromised elderly people are more likely to develop COVID-19 often along with an atypical presentation and complications making diagnosis and management difficult.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 86%
See 2 more Smart Citations
“…COVID-19 patients who are older, males, malnourished or diabetic are more prone to develop AKI. 15 In current study, patients with higher age had AKI more than patients with relatively lower age as also reported by other studies. 10,13,15 This may be due to immunocompromised elderly people are more likely to develop COVID-19 often along with an atypical presentation and complications making diagnosis and management difficult.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 86%
“…15 In current study, patients with higher age had AKI more than patients with relatively lower age as also reported by other studies. 10,13,15 This may be due to immunocompromised elderly people are more likely to develop COVID-19 often along with an atypical presentation and complications making diagnosis and management difficult. 16 Apart from COVID-19, age related structural and functional changes in kidneys leading to reduced renal mass, functioning nephron number and baseline kidney function along with increased likelihood of dehydration, reno-vascular occlusion and impairment of renal auto-regulation also make elderly people highly vulnerable to AKI.…”
Section: A H E a D O F P R I N Tsupporting
confidence: 86%
See 1 more Smart Citation
“…Several studies have reported that inflammatory markers in COVID-19 are predictive both for the occurrence and severity of AKI (15)(16)(17)(18). Severe lung injury is associated with the overproduction of pro-inflammatory cytokines which can increase the risk of AKI (19), as was documented, at least experimentally, even before the COVID-19 pandemic (20).…”
Section: Discussionmentioning
confidence: 93%
“…Biomarkers of systemic inflammation, including IL-6, C-reactive protein (CRP), D-dimer, and ferritin, have been associated with severe COVID-19 infection in general as well as with severe AKI ( 35 ). Husain-Syed et al ( 36 ) were the first to report on the association of urinary biomarkers beyond proteinuria and hematuria with AKI in patients with COVID-19.…”
Section: Pathogenesismentioning
confidence: 99%